Konstuksi Filosofis Akad Mudharabah Dan Relevansinya Dengan Praktik Perbankan Syariah - Imam Buchari (Masyrif : Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
The mudharabah contract has been known since the Arab era of ignorance, until it was used as an alternative to overcome economic problems at the beginning of the hijrah. Therefore, this contract must be understood comprehensively, not only from a definitive perspective, but also from a historical and philosophical perspective. Because this is the basis for the mudharabah contract being legalized in Islamic muamalah practice. At a practical level in the distribution of funds in sharia banking, mudharabah contracts are always less popular than murabahah contracts and other contracts, even though in terms of the radius of economic benefit mudharabah contracts are higher. Therefore, the philosophical construction of a muamalah contract must be explained so that its relevance can be found with the practice carried out. This research uses qualitative methods with the type of library research (literature review). Data sources were obtained from various literary sources, in the form of books, textbooks and other supporting literature using descriptive analysis methods to explain the problem being studied and its relationship with the phenomenon being analyzed. Sharia banking must comply with the profit and loss philosophy inherent in it. This becomes a juridical dilemma for Islamic banking because in practice it is less relevant to its philosophical construction. Transforming the muamalah contract from classical jurisprudence concepts to banking practice cannot be separated from two fundamental problems. First, problems of a philosophical-conceptual-paradigmatic nature. Second, implementation-operational-empirical problems. Prioritizing philosophical-paradigmatic aspects without any implementation efforts will make Islamic banking a mere utopia. On the other hand, prioritizing the empirical-implementation aspect without first building a philosophical-paradigmatic foundation will actually make Islamic banks lose direction as an economic business building that stands on the rubble of uncertainty. So these two aspects need to be harmonized on an ongoing basis to achieve the fundamental goals of muamalah in Islam.